PENGEMBANGAN APLIKASI SICERNA BERBASIS ANDROID UNTUK MENINGKATKAN PEMAHAMAN KONSEP SISWA KELAS V SD PADA MATERI SISTEM PENCERNAAN MANUSIA - Andini Nurul Allika; Ali Ismail; Regina Lichteria Panjaitan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop an android-based SICERNA application as a learning medium to improve the conceptual understanding of fifth grade elementary school students on the human digestive system material. The method used is Research and Development (R&D) with the ADDIE model which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. The subjects of the study were 32 fifth grade students of SDN Genteng 1. Data collection instruments included interviews, questionnaires, and tests. The results of the media expert validation showed an average score of 90.7%, while the results of the material expert validation obtained a score of 93.5%, both of which are included in the very decent category. Students' responses to the SICERNA application using the System Usability Scale (SUS) instrument obtained a score of 91, which is included in the very good category. The test results showed that the average pretest score was 47.53, while the average posttest score increased to 75.78, and the results of the Paired Sample t-Test showed a significance value (Sig.) Of 0.000 <0.05, which means that there was an increase in students' conceptual understanding after using the learning application. Product effectiveness test through N-Gain test analysis showed an average score of 0.5816, which is in the moderate category, and effectiveness of 58.16%, which is included in the fairly effective category. Thus, the SICERNA application is declared feasible and effective to be used as a science learning media and can be considered as an effective solution to improve students' conceptual understanding of the human digestive system material.